Characterization of buffalo production of northeast of Italy - Giovanni Bittante; Luigi Gallo; Massimo De Marchi; Alessio Cecchinato; Francesco Tiezzi (Italian Journal of Animal Science, 2010)
Aim of this study was to characterize the buffalo production in the Veneto region of Italy. Test day records of milk production traits (milk yield, protein, fat, and somatic cell count) of 845 buffalo cows from two herds were analyzed using a linear model. The effects included in the model were herd-test-day, days in milk, and parity. Days in milk was the most important source of variation for milk yield, protein, and fat. The patterns of milk yield traits across lactation followed the typical trend of buffalo cows. Results allowed a preliminary characterization of buffalo production in north of Italy.